Activation of protein kinase R in the manganese-induced apoptosis of PC12 cells. (September 2020) - Yagyu, Kazuya; Hasegawa, Yuto; Sato, Mina; Oh-hashi, Kentaro; Hirata, Yoko
Highlights: The PKR inhibitor C16 strongly prevents manganese-inducedapoptosis in PC12 cells. Manganese induces the proteolytic activation of PKR in PC12 cells. The Inhibition of PKR enhances the cytoprotective responses, such asthe ERK pathway and HO-1. Abstract: Manganese neurotoxicity leads to Parkinson-like symptoms associated with the apoptotic cell death of dopaminergic neurons. Protein kinase R (PKR) is a serine/threonine-specific protein kinase that has been implicated in several cellular signal transduction pathways, including the induction of apoptosis. Here, we investigated the role of PKR in the manganese-induced apoptosis of dopamine-producing pheochromocytoma PC12 cells. Manganese (0.5 mM) induced the proteolytic cleavage of PKR and caspase-3, DNA fragmentation, and cell death, which were prevented by the co-treatment of PC12 cells with a PKR specific inhibitor, C16 in a concentration-dependent manner. C16 did not affect the manganese-induced activation of the c-Jun N-terminal kinase (JNK)/p38 mitogen-activated protein kinase (MAPK) pathway, indicating that PKR functions downstream of JNK and p38 MAPK. In contrast, C16 triggered the activation of the p44/42 MAPK (ERK1/2) pathway and induced hemoxygenase-1, both in the absence and presence of manganese. PKR is reportedly involved in endoplasmic reticulum (ER) stress-induced apoptosis. Manganese activated all three branches of the unfolded protein response in PC12 cells; however, this effect was very weak compared with the ER stress induced by the well-known ER stress inducers thapsigargin and tunicamycin. Moreover, C16 did not affect manganese-induced ER stress at concentrations that almost prevented caspase-3 activation and DNA fragmentation. These results suggest that PKR is involved in manganese-induced apoptotic cell death and stress response, such as the activation of the p44/42 MAPK pathway and the induction of hemoxygenase-1. Although manganese induced a faint, but typical, ER stress, these events contributed little to manganese-induced apoptosis.